Molecular diagnosis of Toxoplasma gondii infection in Libya - Gashout, Aisha (BMC Infect Dis, 2016)
BACKGROUND: Toxoplasma gondii infections are prevalent in humans and animals throughout Libya. Current diagnosis is based on detection of Toxoplasma-specific IgM and IgG. In this study, we established and optimized a diagnostic PCR assay for molecular diagnosis of T. gondii in Libya. METHODS: From January to December, 2010, 177 blood and serum samples were collected from suspected patients. This includes: 140 women who have had spontaneous abortions, 26 HIV-positive patients, nine patients with leukemia and lymphoma, and two infants with ocular infection. Samples were screened for anti-Toxoplasma IgG and IgM antibodies before DNA extraction. The surface antigen gene 2 (SAG2) was targeted in a semi-nested PCR to amplify a 999 bp and a 614 bp fragment in the first and the second run respectively. RESULTS: A total of 54/140 (38.5 %) women who have had spontaneous abortions, 23/26 (88 %) HIV patients, 6/9 (66.6 %) of the leukaemia and lymphoma patients, and one child with ocular infection were seropositive for anti-Toxoplasma IgG and/or IgM. Genomic DNA was extracted from 38 selected seropositive samples. The PCR was sensitive enough to detect DNA concentration of 12 ng/μL. PCR analysis was performed for 38 selected seropositive patients (16 women who have had spontaneous abortions, 15 positive HIV patients, six leukaemia patients and one child with ocular infection). Our designed primers were successfully amplified in 22/38 (57.9 %) samples; 5/12 (35.7 %) from serum and 17/26 (65.8 %) from whole blood samples. All PCR positive samples were IgG-positive except two samples which were IgM and IgG & IgM-positive serum samples respectively. The semi-nested PCR confirmed five more samples. These included two leukaemia and two HIV-positive whole blood samples and one serum sample from an aborted woman. CONCLUSION: The ability of PCR to diagnose active toxoplasmosis is needed in immunocompromised patients and congenital toxoplasmosis cases, especially when serological techniques fail. For the first time in Libya, we established and optimized semi-nested PCR of SAG2 gene. The developed PCR method was able to detect as little as 12 ng/μL of T. gondii DNA and was useful to diagnose the diseases in women who have had spontaneous abortions, HIV-positive patients, patients with leukemia and lymphoma, and infants with ocular infection.